The Influence of Financial Factors on Stock Performance and Their Implication on Firm Value in Coal Subsector Companies Listed on The Indonesia Stock Exchange using SEM PLS - Triesna Ratulina,; Prabowo, Heru; Heikal, Jerry (Jurnal Indonesia Sosial Sains, 2025)
The purpose of this study is to examine the impact of financial factors on company value and stock performance in coal subsector companies listed on the Indonesia Stock Exchange. The study is based on the necessity of understanding how financial indicators such as profitability, leverage, liquidity, and corporate actions influence firm value and investor perception, especially in capital-intensive industries that are extremely sensitive to external swings. Previous research has shown conflicting results, indicating the need for additional empirical examination, particularly in Indonesia's energy sector setting. The study adopts a quantitative approach called Structural Equation Modeling - Partial Least Squares (SEM-PLS). The sample consists of 57 observations gathered specifically from coal company annual reports for the years 2023-2024. Exogenous factors (X) include profitability (ROA, ROE), leverage (DER), liquidity (CR), and corporate action (DIV). Endogenous variables (Y) include Stock Performance (Stock Return) and Firm Value (PBV). The study shows that only leverage has a substantial and favourable effect on stock performance (path coefficient = 0.331, p-value = 0.005). Other variables, including profitability, liquidity, and corporate actions, have no substantial impact on firm valuation or stock performance. These findings imply that, in the coal sector, external factors and market mood may be more important than traditional financial measures in determining business value and investor reactions